Neutrophil to lymphocyte ratio as an indicator of the malignant behaviour of hepatocellular carcinoma. Issue 7 (23rd March 2016) - Okamura, Y; Sugiura, T; Ito, T; Yamamoto, Y; Ashida, R; Mori, K; Uesaka, K
Abstract: Background: The preoperative serum neutrophil to lymphocyte ratio (NLR) has been associated with survival in patients with hepatocellular carcinoma (HCC). However, it is still unclear what the NLR reflects precisely. This study aimed to elucidate the relationship between the NLR and TNM stage, and the role of NLR as a prognostic factor after liver resection for HCC. Methods: This retrospective study enrolled patients who underwent liver resection as initial treatment for HCC. The best cut-off value of serum NLR was determined, and overall survival was compared among patients grouped according to TNM stage (I, II and III). Results: The best cut-off value for NLR was 2·8. A high preoperative NLR was more frequently associated with poor overall survival than a low preoperative NLR after resection for TNM stage I tumours (5-year survival 45·0 versus 76·4 per cent, P < 0·001), but not stage II ( P = 0·283) or stage III ( P = 0·155) tumours. Among patients with TNM stage I disease, the proportion of patients with extrahepatic recurrence was greater in the group with a high preoperative NLR than in the low-NLR group ( P = 0·006). In multivariable analysis, preoperative NLR was the strongest independent prognostic risk factor for overall survival in TNM stage I (hazard ratio 2·69, 95 per cent c.i. 1·57 to 4·59; P < 0·001). Conclusion: Preoperative NLR was an important prognostic factor for TNM stage I HCC after liver resection with curative intent. These results suggest that the NLR may reflect the malignant potential of HCC. Abstract : Potential indicator of prognosis